Physicochemical and sensory analysis of Sauvignon Blanc wines from mechanically pruned vines in Quinta do Gradil treated with municipal solid waste compost - Silva, Pedro Manuel Fernandes (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto